Sleep quality among clinical postgraduate students: a cross-sectional study in Kerala, India - Gopinathan Bhaskaran Gopika; GK Mini; Ameer Ameera; R. Parvathi; P. K. Malavika; Reshma George; Kamala Swarnam; Marthanda Pillai A (BMC Public Health)
Abstract Background Sleep disturbances and stress are common among postgraduate medical students, adversely affect their physical and mental health, academic performance, and patient care. However, the existing evidence does not provide a comprehensive understanding of sleep pattern of medical students in India. We studied sleep pattern and associated factors of clinical medical postgraduate students in Kerala state of India. Methodology This cross-sectional study assessed sleep patterns, lifestyle behaviors, and stress levels among 150 postgraduate medical students (aged between 25 and 44 years) from four medical institutions (one government and three private) in Kerala, India. Data were collected using a pretested structured questionnaire. Questions regarding socio-demographics, work pattern and lifestyle factors were also included. We used Pittsburgh Sleep Quality Index (PSQI) to evaluate sleep quality, and the Perceived Stress Scale-10 (PSS-10) to measure stress levels. Both bivariate and multivariate analysis were performed. Results The prevalence of poor sleep quality was 62.7% (95% confidence interval (CI): 54.4–70.4%), based on the PSQI. Stress levels, measured by the PSS-10, reported that 10.7% (95% CI: 6.2–16.7%) had severe stress. Medical specializations, lack of exercise, family relationship challenges, social anxiety, and severe stress were significantly associated with poor sleep. Those who were having severe stress were more likely to report poor sleep quality compared to their counterparts (adjusted odds ratio (AOR):11.61, CI:1.35–99.39). Medical post graduates were more likely to report poor sleep quality compared to the surgical specialty (AOR: 2.27, CI:1.06–4.87). Conclusion Poor sleep quality and stress are highly prevalent among postgraduate medical students in Kerala. Better management of sleep hygiene by physicians is likely to increase the advice and treatment provided for their patients’ sleep quality.